The overexpression of the pine transcription factor PpDof5 in Arabidopsis leads to increased lignin content and affects carbon and nitrogen metabolism. Issue 4 (7th October 2015) - Rueda‐López, Marina; Cañas, Rafael A.; Canales, Javier; Cánovas, Francisco M.; Ávila, Concepción
Abstract : PpDof 5 is a regulator of the expression of glutamine synthetase (GS; EC 6.3.1.2) genes in photosynthetic and non‐photosynthetic tissues of maritime pine. We have used Arabidopsis thaliana as a model system to study PpDof 5 function in planta, generating transgenic lines overexpressing the pine transcription factor. The overexpression of PpDof 5 resulted in a substantial increase of lignin content with a simultaneous regulation of carbon and nitrogen key genes. In addition, partitioning in carbon and nitrogen compounds was spread via various secondary metabolic pathways. These results suggest pleiotropic effects of PpDof 5 expression on various metabolic pathways of carbon and nitrogen metabolism. Plants overexpressing PpDof 5 exhibited upregulation of genes encoding enzymes for sucrose and starch biosynthesis, with a parallel increase in the content of soluble sugars. When the plants were grown under nitrate as the sole nitrogen source, they exhibited a significant regulation of the expression of genes involved mainly in signaling, but similar growth rates to wild‐type plants. However, plants grown under ammonium exhibited major induction of the expression of photosynthetic genes and differential expression of ammonium and nitrate transporters. All these data suggest that in addition to controlling ammonium assimilation, PpDof 5 could be also involved in the regulation of other pathways in carbon and nitrogen metabolism in pine trees.